Social predictors of oral hygiene status in school children from suburban Nigeria - Titus Ayodele Oyedele; Morenike Oluwatoyin Folayan; Nneka Maureen Chukwumah; Nneka Kate Onyejaka
Abstract Oral hygiene, which is measured by the status of plaque-free tooth surfaces, is essential for the promotion of oral health. This study aimed to determine the social predictors of good oral hygiene for children in a suburban population in Nigeria. This was a secondary analysis of data. The study participants were 8- to 16-year-old children who were residents in Ile-Ife, which is a suburban population in Nigeria. Information on the age, gender, socioeconomic status, family structure, number of siblings and birth rank of each study participant was retrieved from the an interviewer-administered questionnaire. Oral hygiene status was determined through a simplified-oral hygiene index (OHI-S) and categorized as good, fair and poor. The association between oral hygiene status and sociodemographic variables was determined. The predictors of good oral hygiene were determined using a binomial regression analysis. Data on 2,107 individuals were retrieved, of which 44.8% had good oral hygiene and 17.1% had poor oral hygiene. The odds of having good oral hygiene were reduced for children who were 13 to 16 years old (p = 0.02) or male (P=0.002) and children with low socioeconomic status (p ≤ 0.001). The odds of having good oral hygiene increased for children who were last-born compared with those who were first-born (p = 0.02). Age, gender, socioeconomic status and birth-rank were significant social predictive factors of oral hygiene status among the study population. Based on these findings, targeted interventions can be conducted to improve the oral hygiene status of children and adolescents with these social profiles.